Pendampingan Pemanfaatan Aplikasi Kasir Pintar sebagai Solusi Digitalisasi Administrasi di Koperasi Putri Pondok Pesantren Nurul Qur’an Ponorogo - Annisa Ayuning Tyas; Khoirul Fathoni (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research examines the implementation of smart cashier technology as a digital administration solution in the Nurul Qur’an Ponorogo Islamic Boarding School cooperative. The study addresses the challenges of manual reporting, which often leads to delays and discrepancies. Using the ABCD (Asset Based Community Development) approach with data from observation, interviews, and documentation, findings show that the kasir pintar application improves transaction management, stock control, and financial reporting by providing real-time updates, faster service, and reduced errors. Despite challenges such as unstable internet and limited digital literacy, these were mitigated through backup internet, training, and additional devices. Overall, the application effectively enhances efficiency, transparency, and supports the economic independence of pesantren cooperatives, with future research recommended on its long-term impact on student welfare and sustainable growth.